ANALISIS KEBIJAKAN HUTANG DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - sesi, sesiliana; Haposan, Haposan Banjarnahor, S.E., M.SI. (LPPM Universitas Putera Batam, 2022)
In business the importance of strategy for achieving goals, profits and profitability is deciding how to make money each year. The responsibility strategy is identified by providing subsidies for company activities, expansion and investigation, and improving company implementation. Profitability is the company's ability to create (profit) all of its resources and capital in proportion to the contract. That studies aim to determine the effects of debt policy and profitabilities on dividend policies in companies in Manufacturing Companies on the Indonesia Stock Exchange. This research is a quantitative research. Participants in this study were all manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample size of this research is 9 companies. The results of the study conclude that debt policy does not have a significant negative effect on dividend policy in manufacturing companies on the Indonesia Stock Exchange. However, profitability partially has a significant effect on dividend policy in manufacturing companies on the Indonesia Stock Exchange. And debt policy and profitability simultaneously have a significant effect on dividend policy in manufacturing companies on the Indonesia Stock Exchange